Las primeras obras completas de sor Juana Inés de la Cruz (1714-1715 y 1725) (Revista de Crítica Literaria Latinoamericana, 2021)
Neither the editions published in 1951-1957, nor the facsimile of 1995 of the works of the Hieronymus poet, sister Juana Inés de la Cruz, were the first anniversaries or editorial projects to circulate (and sell) her complete works. In 1714- 1715 another anniversary (20th of her death) meant the same for two editors: José Rodríguez y Escobar and Francisco Lasso. Ten years later, Ángel Pascual Rubio, another printer from Madrid, did the same—and better. In this article I will analyze these antique productions in their contexts, and the clues that the paratexts give us to understand if they were in fact “complete works” sold as such, and what that meant for the universe of sor Juana’s printed books.
Keywords: sister Juana Inés de la Cruz; complete works; edition; paratext